Development of a complex intervention to improve health literacy skills. (31st July 2013) - Austvoll‐Dahlgren, Astrid; Danielsen, Stein; Opheim, Elin; Bjørndal, Arild; Reinar, Liv Merete; Flottorp, Signe; Oxman, Andrew David; Helseth, Sølvi
Abstract Background Providing insight into the developmental processes involved in building interventions is an important way to ensure methodological transparency and inform future research efforts. The objective of this study was to describe the development of a web portal designed to improve health literacy skills among the public. Methods The web portal was tailored to address three key barriers to obtaining information, using the conceptual frameworks of shared decision‐making and evidence‐based practice and based on explicit criteria for selecting the content and form of the intervention. Results The web portal targeted the general public and took the form of structured sets of tools. Content included: an introduction to research methods, help on how to find evidence‐based health information efficiently based on the steps of evidence‐based practice, an introduction to critical appraisal, information about patient participation rights in decision‐making, and a decision aid for consultations. Conclusions The web portal was designed in a systematic and transparent way and address key barriers to obtaining and acting upon reliable health information. The web portal provides open access to the tools and can be used independently by health care users, or during consultations with health professionals.